Differences in the C-reactive protein between individuals with different categories of Alistipes within each group IL-6 and different categories of BMI within each group of IL-6, in participants with SLE. - Lourdes Chero-Sandoval (22683418) (2025)
Green boxes represent low abundance of Alistipes, and blue boxes represent high abundance of Alistipes (A). Relationship between BMI categories and C-reactive protein in patients with SLE. Green boxes represent participants with low BMI and blue boxes represent high BMI (B).